2004
DOI: 10.1002/app.13716
|View full text |Cite
|
Sign up to set email alerts
|

Solid polymer electrolytes. VII. Preparation and ionic conductivity of gelled polymer electrolytes based on poly(ethylene glycol) diglycidyl ether cured with α,ω‐diamino poly(propylene oxide)

Abstract: ABSTRACT:Crosslinked polymer electrolyte networks were prepared from poly(ethylene glycol) diglycidyl ether blended with an epoxy resin (diglycidyl ether of bisphenol A) in different ratios and then cured with ␣,-diamino poly(propylene oxide) in the presence of lithium perchlorate (LiClO 4 ) as a lithium salt. The ionic conductivities of these polymer electrolytes were determined by alternating current (AC) impedance spectroscopy. Propylene carbonate (PC) was used as a plasticizer to form gelled polymer electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…The PEGDGE-based epoxy resin has modest mechanical properties (Young's modulus 38 of around 6 MPa) compared to traditional structural epoxy resins (such as bisphenol-A based epoxy with a Young's modulus of around 3 GPa), but offers reasonable ionic conductivity. 39 As shown in Table 2 properties and the tendency to promote delamination in the composites make them less ideal than glass fibre (GF) fabrics as separators in multifunctional structural supercapacitors. The thickness of GF used in this work was around 160 µm, because the commercially available, lighter fabrics were not sufficiently dense to prevent short-circuiting.…”
Section: Electrochemical Characterisation Of Structural Supercapacitorsmentioning
confidence: 99%
“…The PEGDGE-based epoxy resin has modest mechanical properties (Young's modulus 38 of around 6 MPa) compared to traditional structural epoxy resins (such as bisphenol-A based epoxy with a Young's modulus of around 3 GPa), but offers reasonable ionic conductivity. 39 As shown in Table 2 properties and the tendency to promote delamination in the composites make them less ideal than glass fibre (GF) fabrics as separators in multifunctional structural supercapacitors. The thickness of GF used in this work was around 160 µm, because the commercially available, lighter fabrics were not sufficiently dense to prevent short-circuiting.…”
Section: Electrochemical Characterisation Of Structural Supercapacitorsmentioning
confidence: 99%
“…The leakage current could be ascribed mainly to an electronic current that resulted from irreversible decomposition of the mobile LiClO 4 /PC. It was reported that the polymer chains in the solvent-free P(EO-co-PO) matrices could be polarized in an electrical field [35]. The similarity in the leakage current for these two capacitors reflects the stability of the immobile polymer network during polarization.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, the addition of PC in the present work was to reduce the complexation degree of Li + with the oxygen and nitrogen atoms and thus to increase the segmental mobility of the polymer. Also, the PC plasticizer might have formed a local solvent channel for ion motion in the gel electrolyte [33,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S8 (Supporting Information) presents the impedance data in a Nyquist plot. The ionic conductivity of the electrolytes was determined according to Equation ,σ=RI1S1dwhere σ represents ionic conductivity, R I is the real axis intercept in the Nyquist plot, S is the geometric area of the electrolyte–electrode interface, and d is the distance between the two electrodes . Figure presents the temperature dependence of the electrolyte ionic conductivities in the Arrhenius plot.…”
Section: Resultsmentioning
confidence: 99%